FAKTOR-FAKTOR YANG MEMENGARUHI KEBIJAKAN HUTANG (Media Riset Akuntansi, 2022)
The purpose of this study was to examine the factors that affect debt policy. In this study, the population were all manufacturing companies that basic and chemical sectors which were listed on the Indonesia Stock Exchange (IDX) during 2016-2018. The sampling technique was purposive sampling.  Based on method, the sample was 66 companies and The research model used is a quantitative research model using with secondary data. This study used a multiple linear regression analysis. The results showed that profitability and company size effect on debt policy, meanwhile the dividend policy and asset structure does not effect on debt policy. The result show that the lower the dividend policy, meanwhile the asset structure the result show that how many fixed assets owned by the company will not affect the debt policy.